MiR-30e induces apoptosis and sensitizes K562 cells to imatinib treatment via regulation of the BCR–ABL protein. Issue 2 (28th January 2015) - Hershkovitz-Rokah, Oshrat; Modai, Shira; Pasmanik-Chor, Metsada; Toren, Amos; Shomron, Noam; Raanani, Pia; Shpilberg, Ofer; Granot, Galit
Abstract: Chronic myeloid leukemia (CML) is a disorder of hematopoietic stem cell carrying the Philadelphia (Ph) chromosome and an oncogenic BCR–ABL fusion gene. Tyrosine kinase inhibitors (TKIs) of the BCR–ABL kinase are the treatment of choice for CML patients. Imatinib was the first TKI used in clinical practice with excellent results. MicroRNAs (miRNAs) are short non-coding regulatory RNAs that control gene expression and play an important role in cancer development and progression. Aberrant miRNA expression profiles have been shown to be characteristic of many cancers. Here, we demonstrate that miR-30e is expressed at low levels in CML cell lines and patient samples. Bioinformatics analysis reveals a putative target site for miR-30e in the 3′-untranslated region (UTR) of the ABL gene. In agreement, luciferase assay verified that miR-30e directly targets ABL. Enforced expression of miR-30e in K562 cells suppressed proliferation and induced apoptosis of these cells and sensitized them to imatinib treatment. These findings strongly suggest that miR-30e acts as a tumor suppressor by downregulating BCR–ABL expression. Up-regulation of miR-30e in CML cells may therefore have a therapeutic efficacy against this disease.